Study about the implementation of E-government and digital government policies from the G2G approach: systematic review (2024)
The research on e-government and digital government policies has grown due to increased technological use by both governments and citizens. However, there remains a gap in understanding the government-to-government (G2G) aspect. That being said, the aim of this paper was to determine the variables that influence the implementation of e-government and digital government public policies in the Government to Government (G2G) approach. The study employed the 2020 PRISMA method, involving two phases. Firstly, document identification and sample selection led to 46 documents being included. Secondly, findings were coded, analyzed, and synthesized. The study highlighted the significance of variables like information exchange, information security, citizen engagement, policy-related decision-making, human resources, and inter-agency services. These factors serve as the foundational elements for successful e-government and digital government policy implementation within the G2G context.